'Doing' Social Justice in Early Childhood: The Potential of Leadership. (December 2013) - Hard, Louise; Press, Frances; Gibson, Megan
Early childhood education has long been connected with objectives related to social justice. Australian early childhood education and care (ECEC) has its roots in philanthropic and educational reform movements prevalent at the turn of the twentieth century. More recently, with the introduction of the National Early Childhood Reform Agenda, early childhood education has once more been linked to the achievement of aims associated with redressing inequality and disadvantage. The authors argue that educational leaders have an obligation to promote equity as they articulate the needs of marginalised students who are traditionally disadvantaged while they also work towards challenging the social order that affords this circumstance of inequity to exist. Drawing on extant literature, including data from two previously reported Australian studies in which leadership emerged as having a transformational impact on service delivery, this article examines the potential of early childhood leadership to generate 'socially just' educational communities. With reference to critical theory, the authors argue that critically informed, intentional and strategic organisational leadership can play a pivotal role in creating changed circumstances and opportunities for children and families. Such leadership includes positional and distributed elements, articulation of values and beliefs, and collective action that is mindful and informed.